Frequent immediate knowledge of results enhances the increase of throwing velocity in overarm handball performance - Stirn, I.; Carruthers, J.; Sibila, M.; Pori, P. (Journal of Human Kinetics, 2017)
In the present study, the effect of frequent, immediate, augmented feedback on the increase of throwing velocity was investigated. An increase of throwing velocity of a handball set shot when knowledge of results was provided or not provided during training was compared. Fifty female and seventy-three male physical education students were assigned randomly to the experimental or control group. All participants performed two series of ten set shots with maximal effort twice a week for six weeks. The experimental group received information regarding throwing velocity measured by a radar gun immediately after every shot, whereas the control group did not receive any feedback. Measurements of maximal throwing velocity of an ordinary handball and a heavy ball were performed, before and after the training period and compared. Participants who received feedback on results attained almost a four times greater relative increase of the velocity of the normal ball (size 2) as compared to the same intervention when feedback was not provided (8.1 ± 3.6 vs. 2.7 ± 2.9%). The velocity increases were smaller, but still significant between the groups for throws using the heavy ball (5.1 ± 4.2 and 2.5 ± 5.8 for the experimental and control group, respectively). Apart from the experimental group throwing the normal ball, no differences in velocity change for gender were obtained. The results confirmed that training oriented towards an increase in throwing velocity became significantly more effective when frequent knowledge of results was provided.